Enhancing self-concept in patients with mental disorders through deep breathing exercises and community mental health nursing training: A quasi-experimental study - Ibrahim Rahmat; Mohammad Hendra Setia Lesmana; Soewadi; Mohammad Hakimi; Kiki Amanda Fatmawati (Physical Therapy Journal of Indonesia, 2025)
Background: Patients with mental diseases with low self-concept are more likely to engage in maladaptive behavior, isolate themselves, and relapse. This study aimed to examine the effectiveness of deep breathing exercise and community mental health nursing (CMHN) training in improving the self-concept quality of patients with mental disorders. Methods: The study used a quantitative quasi-experimental approach with a non-equivalent control group. A total of 235 individuals were randomly selected from ten primary health facilities in Bantul, Yogyakarta, including 120 in the intervention group (combination of deep breathing exercises and CMHN training) and 115 in the control group (self-directed study only). Eligible participants were cooperative patients with mental disorders in the maintenance or health promotion phase, while those unwilling to follow the training protocol were excluded. Self-concept served as the dependent variable, measured using a self-concept questionnaire. Data were analyzed using paired t-tests in SPSS, with statistical significance set at p < 0.05. Results: The intervention group showed a significant increase in mean self-concept scores, from 105.2 pretest to 110.0 posttest (p = 0.004), while no significant change was observed in the control group (p = 0.092). Conclusion: Integrating deep breathing exercises with CMHN training improves the self-concept of individuals with mental illnesses during the maintenance and health promotion stages.